DIETARY DOUBLE-THINK. Issue 52 (4th June 2019) - Easton, Christina
Abstract : This article discusses how difficult it is to be morally consistent when choosing what to eat. Applying a moral justification in a consistent manner may result in some unorthodox diets. I distinguish two ways in which we might be inconsistent in our approach to food. We might fail to apply our morals in a consistent way, or we might fail to put our morals into practice at all . I argue that the latter represents a greater failing. Given the complexity of making food choices, the former is more excusable.